2018
DOI: 10.1038/s41598-018-34471-y
|View full text |Cite
|
Sign up to set email alerts
|

Identification and antitumor activity of a novel inhibitor of the NIMA-related kinase NEK6

Abstract: The NIMA (never in mitosis, gene A)-related kinase-6 (NEK6), which is implicated in cell cycle control and plays significant roles in tumorigenesis, is an attractive target for the development of novel anti-cancer drugs. Here we describe the discovery of a potent ATP site-directed inhibitor of NEK6 identified by virtual screening, adopting both structure- and ligand-based techniques. Using a homology-built model of NEK6 as well as the pharmacophoric features of known NEK6 inhibitors we identified novel binding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 60 publications
0
19
0
Order By: Relevance
“…NEK6 has been proven to be a target of miR-506-3p in RB 18. Growing evidence showed that NEK6 played crucial roles in tumorigenesis 34,35. Here, we determine whether HOXA11-AS can regulate NEK6 expression.…”
Section: Discussionmentioning
confidence: 86%
“…NEK6 has been proven to be a target of miR-506-3p in RB 18. Growing evidence showed that NEK6 played crucial roles in tumorigenesis 34,35. Here, we determine whether HOXA11-AS can regulate NEK6 expression.…”
Section: Discussionmentioning
confidence: 86%
“…First-line chemotherapy for ovarian cancer, which is usually based on a platinum drug, has little impact on the overall survival of patients. Combination treatment with carboplatin and a taxane leads to a better overall clinical response than anthracyclines in patients with ovarian cancer [ 31 , 32 ]. However, the slight improvement in survival is associated with a significant increase in adverse effects, underscoring the need to identify and design novel therapeutic strategies.…”
Section: Discussionmentioning
confidence: 99%
“…De Donato et al (2015) found that NEK6 overexpression decreased cisplatin sensibility in A2780 cells, a human ovarian carcinoma cell line [157]. Another study by De Donato et al (2018) found a compound named compound 8, that binds to NEK6 and NEK1 kinase domains and inhibits their kinase activities, increasing cisplatin sensibility in PEO1 cells, another ovarian cancer cell line [158]. Jeon et al (2010) [159] identified that the ectopic expression of NEK6 in JB6 Cl41 cells phosphorylates S727 of STAT3 (Signal transducer and activator of transcription 3), increasing transcriptional activation activity [159].…”
Section: Nek6mentioning
confidence: 96%